Collection, characterization and evaluation of aloe vera (L) burm. f. germplasm - Abhila S R (Department of Plantation Crops and Spices, College of Agriculture, 2007)
The present study titles “Collection, characterization and evaluation of Aloe vera (L) Burm.f.germplasm” was conducted at the Department of Plantation crops and spices, College of Agriculture, Vellayani during the period April 2006 – March 2007.